2020
DOI: 10.1038/s41598-020-71004-y
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms protect airborne green microalgae during long distance dispersal

Abstract: Viable microalgae occur in the air. Whether they can survive the stresses such as UV, desiccation and freezing temperatures at high altitudes during long distance dispersal is rarely studied. if yes, what mechanisms confer the tolerance? four freshwater airborne green microalgae were isolated from Dongsha Atoll in the South China Sea, classified as Scenedesmus sp. DSA1, Coelastrella sp. DSA2, Coelastrella sp. DSA3 and Desmodesmus sp. DSA6 based on their morphologies and ITS sequences. their survival rates unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 33 publications
2
4
0
Order By: Relevance
“…Statistical analysis showed that the presence of microalgae in the atmosphere is not dependent on a single meteorological variable but on a combination of various environmental parameters, as stated by other researchers (Chiu et al 2020 ; Chu et al 2013 ; Sharma and Singh 2010 ; Tormo et al 2001 ). In this study, similarly to Tormo et al ( 2001 ), a significant negative correlation was proven between the concentration of airborne microalgae and relative humidity.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…Statistical analysis showed that the presence of microalgae in the atmosphere is not dependent on a single meteorological variable but on a combination of various environmental parameters, as stated by other researchers (Chiu et al 2020 ; Chu et al 2013 ; Sharma and Singh 2010 ; Tormo et al 2001 ). In this study, similarly to Tormo et al ( 2001 ), a significant negative correlation was proven between the concentration of airborne microalgae and relative humidity.…”
Section: Discussionsupporting
confidence: 54%
“…Others metabolise various pigments, capable of absorbing solar energy of different wavelengths (Roy et al 2011 ). Some genera (e.g., Coelastrella or Scenedesmus ) have multi-layered UV-resistant coats formed by dense cell walls, various antioxidants, and carotenoids (Chiu et al 2020 ). In this study, carotenoid accumulation was observed in the genus Bracteacoccus , which may largely explain its clear dominance in the samples throughout the studied years.…”
Section: Discussionmentioning
confidence: 99%
“…UTEX 3007 (54), can potentially survive a variety of atmospheric stressors because of intracellular desiccation resistance-promoting sugars (36,54). Some green algae isolated from the atmosphere have carotenoids, thick cells walls, and intracellular antioxidants which help them to survive atmospheric stressors (55). Many members of the Trebouxiophyceae have mycosporine-like amino acids in the cytoplasm which help to protect the algae from UV radiation and oxidants (56).…”
Section: Cyanobacteria and Algae In Clouds And Rain 12mentioning
confidence: 99%
“…The procedure for carrying out SEM was described in Chiu et al 24 . For the measurement of photosystem II efficiency (quantum yield, Fv'/Fm'), the cells were cultivated in 1 L flasks containing 150 mL of the ASW-IMK medium until mid-log phase in conditions described above.…”
Section: Cell Count Scanning Electron Microscopy (Sem) and Measuremen...mentioning
confidence: 99%